Diffusion tensor imaging of cervical spinal cord: A quantitative diagnostic tool in cervical spondylotic myelopathy - (:unkn) unknown (MEDKNOW PUBLICATIONS & MEDIA PVT LTD, 2016)
Background: Diffusion tensor imaging (DTI) is a novel magnetic resonance imaging (MRI) technique potentially able to evaluate the microscopic structural organization of white matter fibers. Aim: This study aimed to compare fractional anisotropy (FA) and apparent diffusion coefficient (ADC) values obtained by DTI in stenotic versus nonstenotic cervical spinal segments of patients with clinical and neurological evidence of cervical spondylotic myelopathy (CSM). Materials and Methods: This prospective study included 21 patients with CSM but without T2 changes on conventional MRI. Diffusion tensor (DT) images from the stenotic and nonstenotic segments of the subjects were obtained. FA and ADC values were estimated and compared with stenotic versus nonstenotic segments. Statistical Analysis: Paired t-test was used [Statistical Package for the Social Sciences (SPSS) 12.0]. Results: In the most stenotic segments, the mean FA value was significantly lower (0.4228 0.1090 vs 0.6884 0.0075, P < 0.001) and the mean ADC value was significantly higher (1.312 0.2405 vs 0.9183 0.1477, P < 0.001) when compared to nonstenotic segments. In addition, there was a negative correlation between FA and ADC values (r = 0.63, P = 0.002). Conclusions: DTI of the cervical spine seems to be a promising novel imaging modality in patients with CSM. Advances in Knowledge: DTI may offer increased diagnostic sensitivity as compared to standard MRI and enables earlier detection of the disease.
Keywords: Apparent diffusion coefficient (ADC); cervical spondylotic myelopathy (CSM); diffusion tensor imaging (DTI); fractional anisotropy (FA); INCREASED SIGNAL INTENSITY; MAGNETIC-RESONANCE IMAGES; NATURAL-HISTORY; COMPRESSION; SURGERY; BRAIN